Successful women think differently - Burton, Valorie (Harvest House Publishers, 2012)
Popular author and professional certified coach Valorie Burton knows that successful women think differently. They make decisions differently. They set goals differently and bounce back from failure differently. Valorie is dedicated to help women create new thought processes that empower them to succeed in their relationships, finances, work, health, and spiritual life.